Reform progress and achievements of China’s incentive policies for pediatric medicine over the last decade - Wang, Qiwei; Ling, Xing; Dai, Zhengli; Wang, Xiaoling; Guo, Wen; Chen, Guiliang (Frontiers in Pharmacology, 2025)
BackgroundThe accessibility of pediatric medicine is a global challenge. The issuance of the “Several Opinions on Ensuring the Use of Children’s Medicine” by six ministries in China in 2014 marked the formation of the policy framework. This study aims to systematically review the progress and achievements of incentive policies for China’s pediatric medicine.MethodsBy analyzing policy documents, clinical trial data, review and approval results, medical insurance directories, volume-based procurement data, as well as adverse reaction reports, the implementation effects of incentive policies for China’s pediatric medicine were assessed.ResultsChina has made progress in legislation, research and development, review and approval, production, access, payment, and use of pediatric medicine. The number and variety of pediatric clinical trials have increased year by year. Some medicine on the Encouraged Research and Submission List of Pediatric Medicine have successfully entered the market. Priority review and approval policies have effectively facilitated the rapid approval of pediatric medicine. However, the availability still needs to be improved, especially in the field of medicine for young children (<6 years).ConclusionAlthough incentive policies for China’s pediatric medicine have achieved favorable effects, the synergy of the policies still needs to be strengthened. It is recommended that the Chinese government place greater emphasis on the introduction of mandatory regulations and incentive policies, enhance the synergy between policies, use a combination of fiscal and medical insurance tools and follow up on the application of new technologies to comprehensively improve the accessibility of pediatric medicine in the future. This might be helpful for guaranteeing the safety, efficacy and economy of pediatric medicine.